A Systematic Review of Flashcards for English Language Teaching (ELT) - Cantika Khaerunnisa Wijaya; Naila Aulia; Nafan Tarihoran (Adisam Publisher, 2025)
Flashcards have long been recognized as a valuable tool in English Language Teaching (ELT), particularly for helping students build and retain vocabulary. With the rise of technology, traditional paper-based flashcards have evolved into digital formats, making them more versatile and widely accessible in language learning. This study aims to analyze trends in flashcard research and explore their impact on vocabulary acquisition, student engagement, and technological integration. This systematic review explores the effectiveness of flashcards in ELT, focusing on primary school students by analyzing studies published between 2020 and 2024. Following the PRISMA framework, relevant studies were selected from databases such as Google Scholar, Mendeley, and Semantic Scholar, ensuring a rigorous screening process based on specific inclusion and exclusion criteria. The findings reveal that flashcards improve vocabulary retention, increase student engagement, and foster motivation. Digital flashcards, in particular, offer interactive features, multimedia support, and ease of access, creating a more engaging and adaptable learning experience. However, challenges such as unequal access to technology and the risk of over-reliance on digital tools must be considered. This review emphasizes the importance of integrating flashcards with other teaching strategies to maximize their impact in ELT classrooms.